Utility of Shadangapaniya in Various Ailments – A Review - Sajeesh; Thakur, Balaji; Prasad, Mahendra; Singh, Bhanu Pratap (International Research Journal of Ayurveda & Yoga, 2024)
Introduction: Ayurveda has mentioned many Kalpanas, one among them is Paniya Kalpana (medicated drinking water). It comes under Upakalapana (derivative) of Kwatha (process of medicated liquid). It is regarded as the most beneficial and potent because it is very easy to digest and readily absorbed by our bodies. Dosha (one which governs and maintains the health), Dhatu (fundamental tissues that constitute the human body), and Mala (metabolic end products) are the components of Sharira (human body), which is governed by Agni (digestive fire). In a healthy state, Sharira (human body) maintains regular physiological functioning; when it is impaired, Sharira (human body) results in various ailments. Shadangapaniya is a special formulation that controls all the aforementioned aspects. Six herbs, including Musta, Parpataka, Ushira, Chandana, Udichya, and Nagara, make up the Shadangapaniya. Materials and methods: The classic Ayurveda literature, including the Charaka Samhita, Sushrutha Samhita, Ashtanga Hridaya, and Bhavprakasha Niganthu books of Dravyaguna Vignana, and other Nighantus. Result and Discussion: Shadangapaniya not only acts on Jwara (fever) but also is useful in various conditions and as well as on various systems. For example, we can give in Rakthapitta (bleeding conditions), Atisara (diarrhea and dysentery), Ati sweda (excessive perspiration), and Trishna (thirst), which will be discussed with references from classical textbooks. Conclusion: Maintaining the equilibrium state of Dosha (one which governs and maintains the health), Dhatu (fundamental tissues that constitute the human body) Mala (metabolic end products), and Agni (digestive fire) is the fundamental goal of all Ayurvedic treatments for ailments. Shadanga Paniya (medicated drinking water made up of six herbs) is a distinctive and popular recipe that preserves the above-mentioned state of equilibrium.